Sanko Plastic Malaysia / Muhammad Haziq Darwisy Rohaizat - Rohaizat, Muhammad Haziq Darwisy (Faculty Of Chemical Engineering, 2022)
This industrial training report of Muhammad Haziq Darwisy bin Rohaizat to undergo an industrial training for duration of 6 months which consist of 24 weeks before completing the Diploma courses. Starting industrial training on 21 February 2022 until 5 August 2022 at Sanko Plastic Malaysia Sdn Bhd which guided by Miss Hidayu binti Abdul Rani and Sir Mohd Haikal bin Mustafa. The purpose of this program is to fulfill the course in order to complete the Diploma as well as graduate from the university. The training refers to work experience that is relevant to professional development prior to graduate. In first chapter this report is defining the term of industrial training and description on industrial training objectives. This part explains the details of objectives of industrial training report and industrial report. The corporation and its departments are described in the second chapter of the report. In third chapter describes about the summary of the duties and various task given in weekly of industrial training activities. The next chapter explain the experience gained during the internship and a few issues encountered in the company. As for the last chapter describe the conclusion after finished the internship. This training gives students a good experience in a real working environment. For example, the challenge to communicate with the workers and staff. At working place student need to be smart in order to choose the suitable words while communicate. Last but not least, trainee also got opportunities to learn a lot of things. Student can learn about the other things from a subject that they learn in university. For example, they can learn about new equipment and machine that they never see and learn during their study period.